Stir bar-sorptive extraction, solid phase extraction and liquid-liquid extraction for levetiracetam determination in human plasma: comparing recovery rates - Priscila Freitas-Lima; Flavia Isaura Santi Ferreira; Carlo Bertucci; Veriano Alexandre Júnior; Sônia Aparecida Carvalho Dreossi; Leonardo Regis Leira Pereira; Américo Ceiki Sakamoto; Regina Helena Costa Queiroz (Universidade de São Paulo, 2015)
Levetiracetam (LEV), an antiepileptic drug (AED) with favorable pharmacokinetic profile, is increasingly being used in clinical practice, although information on its metabolism and disposition are still being generated. Therefore a simple, robust and fast liquid-liquid extraction (LLE) followed by high-performance liquid chromatography method is described that could be used for both pharmacokinetic and therapeutic drug monitoring (TDM) purposes. Moreover, recovery rates of LEV in plasma were compared among LLE, stir bar-sorptive extraction (SBSE), and solid-phase extraction (SPE). Solvent extraction with dichloromethane yielded a plasma residue free from usual interferences such as commonly co-prescribed AEDs, and recoveries around 90% (LLE), 60% (SPE) and 10% (SBSE). Separation was obtained using reverse phase Select B column with ultraviolet detection (235 nm). Mobile phase consisted of methanol:sodium acetate buffer 0.125 M pH 4.4 (20:80, v/v). The method was linear over a range of 2.8-220.0 µg mL-1. The intra- and inter-assay precision and accuracy were studied at three concentrations; relative standard deviation was less than 10%. The limit of quantification was 2.8 µg mL-1. This robust method was successfully applied to analyze plasma samples from patients with epilepsy and therefore might be used for pharmacokinetic and TDM purposes.